HUBUNGAN ANTARA SELF-COMPASSION DENGAN SELF-DISCLOSURE PADA REMAJA DI PANTI ASUHAN TRITUNGGAL SUMBAWA - Triana; Yossy Dwi Erliana; Kartika Mustafa (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2019)
This study aims to determine how is the correlation between self-compassion and self-disclosure, as well as the general picture of self-compassion and self-disclosure in teenagers at Tritunggal Orphanage of Sumbawa. This research uses descriptive quantitative approach. The research subjects were taken using population study approach with 60 teenagers in Tritunggal Orphanage of Sumbawa. Research data were obtained by using research instruments in the form of two scales, namely self-compassion and self-disclosure. The result of this research shows that there is a positive and significant correlation between self-compassion and self-disclosure with correlation coefficient value (rxy) of 0,496 with p value = 0.0001 / p <0.05. Based on the average calculation in general, the general picture of self-compassion and self-disclosure of teenagers in Tritunggal Orphanage of Sumbawa is in high category.